Biodegradation of Biopolymers - Nair, N. R.; Sekhar, V. C.; Nampoothiri, K. M.; Pandey, A.
The concept of biodegradable plastics is receiving significant attention with respect to solid waste accumulation. Enormous efforts have been made in revolutionizing degradable biological materials without any environmental pollution to substitute for oil-based traditional plastics. With the overuse of plastics and increasing pressure being placed on capacities available for plastic waste disposal, the requirement for biodegradable plastics and biodegradation of plastic wastes has obtained immense importance in recent years. Awareness of the impact on the environmental waste problem has awakened research in the area of degradable polymers. Considering the emerging environmental issues, the demand to develop a material that does not burden nature has increased. It is essential to study the microbial degradation of biopolymers to understand what is necessary for biodegradation and the mechanisms involved. Widespread investigations on the biodegradation of plastics have been carried out to overcome the environmental problems associated with synthetic plastic waste. This chapter provides an overview of the degradation mechanisms of biodegradable polymers with particular emphasis on the main parameters affecting the degradation of polymeric biomaterials.
Keywords: BIO-BASED PLASTICS; BIODEGRADABILITY; BIOPOLYMERS; POLYESTERS